Філософські засади музичної естетики нової віденської школи (на прикладі творчості А. Шенберга) - Пославський, А. (Студії мистецтвознавчі, 2008)
The article “Philosophic Roots of New Vienna School’s Musical Aestheties (on the material of Schoenberg’s works)” is devoted to studying the aesthetic features of musical expressionism.